Towards a definition of sound as vibrant matter - Orecchia, Joao Renato (My University, 2016)
This dissertation explores different but related philosophies of material agency - the idea that all matter, human or non-human, carries some kind of agency: a capacity to affect and to be affected, the potential sociopolitical implications of such a viewpoint and the potential of sound art to explore these ideas in an experiential way. I discuss and draw connections between three materialist philosophies: the New Materialism of Gilles Deleuze, Felix Guatarri, Brian Massumi and others, the Vibrant Materialism of Jane Bennett and the Sonic Materialism of Christoph Cox, Steve Goodman, Salomé Voegelin and others. These materialist philosophies understand bodies not as static or complete, but in a constant state of flux, never fully formed but continuously form-ing; always in relation to and affected by the ongoing formation of other material bodies. Advocating the decentralisation of human experience, Vibrant Materialism takes into account material processes beyond the intentions or interventions of humans. Sonic Materialism understands sound as an exemplary illustration of affective matter in flux: always present, always moving, always in flux and always affecting and affected by everything it comes into contact with. As a case study, the collected works of a sound artist named Eleh show how these ideas can be implemented in practice. The research finally culminated in an exhibition of installations exploring the potential of sound to move, to act, to change, to affect and to be affected, towards a definition of sound as vibrant matter.
A thesis submitted to the Faculty of Humanities, in partial fulfilment of the degree of Master of Arts in Digital Arts,University of the Witwatersrand, 2016
Keywords: Computer art; Sound in art